Consumer acceptance and stability of spray dried betanin in model juices. (15th November 2015) - Kaimainen, Mika; Laaksonen, Oskar; Järvenpää, Eila; Sandell, Mari; Huopalahti, Rainer
Highlights: Juice models with spray dried betanin were tested for stability and sensory liking. Anthocyanin and beetroot extract colours were preferred over spray dried beetroot colour. Off-odours from beet were not perceived in juices coloured with spray dried beetroot. Colour stability of model juices was better at −20 °C and 4 °C than at 20 °C and 60 °C. Colour of spray dried beetroot powder retained well when stored at 20 °C. Abstract: Spray dried beetroot powder was used to colour model juices, and the consumer acceptance of the juices and stability of the colour during storage at 60 °C, 20 °C, 4 °C, and −20 °C were studied. The majority of the consumers preferred the model juices coloured with anthocyanins or beetroot extract over model juices coloured with spray dried beetroot powder. The consumers preferred more intensely coloured samples over lighter samples. Spray dried betanin samples were described as 'unnatural' and 'artificial' whereas the colour of beetroot extract was described more 'natural' and 'real juice'. No beetroot-derived off-odours or off-flavours were perceived in the model juices coloured with beetroot powder. Colour stability in model juices was greatly dependent on storage temperature with better stability at lower temperatures. Colour stability in the spray dried powder was very good at 20 °C. Betacyanins from beetroot could be a potential colourant for food products that are stored cold.